Solidarity: Does the Modern Catholic Rights Tradition have Anything to Offer Environmental Virtue Ethics? - Butkus, Russell (Environmental ethics, 2015)
Within the last decade those familiar with environmental ethics have witnessed a resurgence of environmental virtue ethics. According to Louke van Wensveen, ecological virtue language is "rapidly growing" and "represents a distinct moral discourse with an internal unity and logic"—what she calls "an integral discourse." Does the modern Catholic rights tradition (aka Catholic social teaching) have anything to contribute to this ethical discourse? Grounded historically in neo-Thomistic natural law and virtue ethics, Catholic social teaching originated as a response to late ninteenth- and early twentieth-century social and economic crises (e.g., the Great Depression). Out of this application emerged the virtue of solidarity. However, an analysis of recent discourse in environmental virtue ethics shows that the treatment of solidarity as an environmental virtue is rather thin in the literature. Nevertheless, with the development of solidarity and the expanding notion of the common good, inclusive of the planetary commons, in recent Catholic documents, solidarity is "translatable" into the realm of ecological virtue ethics. As an environmental virtue, solidarity should be interpreted as "biophilic solidarity" grounded in the genetic homology of evolutionary speciation, and defined as the consistent habit of character expressed in the recognition of our fundamental interrelatedness with the human and nonhuman. As a virtue biophilic solidarity takes explicit shape in determined active engagement (praxis) to create, promote, and restore the universal common good of creation. In relation to the human-centered Catholic rights tradition, the status of nature is examined drawing on an axiological analysis of nature indicating that the natural world holds a spectrum of values including utilitarian and intrinsic value. The concluding reflection points to the shortfall of environmental virtue ethics without an accompanying social ethic in the interest of an ecological vision for a sustainable society.